2021
DOI: 10.18502/jbe.v7i1.6293
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Number of Household Visit to Health Care Centres in Some Nigeria Communities Using Count Data Regression Models

Abstract: Introduction: The need to model the impact of some demographic indicators on the frequency of household visits to healthcare centres in Nigeria's community is very important for preventing and spreading community diseases. This study aimed to investigate the effect of the patents' age, gender, marital status, type of illness and amount spent on the frequency of visits to community health care centres in Nigeria and to compared Negative Binomial Regression (NBR) and Generalized Poisson Regression (GPR) models t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…According to our findings, in view of the took on model determination standards, the Negative Binomial model performed somewhat better compared to the Summed up Poisson model. This outcome is in accordance with previous study, which analyzed Summed up Poisson relapse and Negative Binomial relapse to pick the best count information model (Adams et al, 2021). When it comes to describing count data with excessive dispersion, their findings indicate that the Negative Binomial regression model is superior.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…According to our findings, in view of the took on model determination standards, the Negative Binomial model performed somewhat better compared to the Summed up Poisson model. This outcome is in accordance with previous study, which analyzed Summed up Poisson relapse and Negative Binomial relapse to pick the best count information model (Adams et al, 2021). When it comes to describing count data with excessive dispersion, their findings indicate that the Negative Binomial regression model is superior.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…This study demonstrates that a unit increase in confirmed laboratory cases will result in a 1.98 percent increase in COVID-19-related deaths and a 1.8% and 1.1% decrease in admissions and discharges from isolation, respectively. Similar to [28][29][30][31][32], this evidence on the negative impact of admitted and discharged cases on COVID-19 prevalence in their investigation into how admission affected the pandemic in populations other than COVID-19. To avoid negative outcomes, certain medical conditions like stroke and acute ST-elevation myocardial infarction necessitate prompt treatment in the hospital; As a result, fewer patient harms are almost certainly associated with fewer hospitalizations for such medical conditions.…”
Section: Discussion Of Findingsmentioning
confidence: 80%
“…At the end of 2015, only 10.3 million (54%) of all HIV patients in this sub-region were receiving antiretroviral therapy. It is also reported that this region had a higher percentage of adult women (59%) than men (44%) accessing therapy during the same period (9)(10)(11). In general, the eastern and southern regions of Africa have shown numerous signs of gradual, modest declines in the mode of HIV occurrence in recent years.…”
Section: Review Of Related Literature On Hiv Prevalence In Subsaharan...mentioning
confidence: 97%